Advanced Energy Materials 2014
DOI: 10.1002/9781118904923.ch9
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Damage in GaN‐Based Materials and Devices

Abstract: A review of electron, proton and neutron damage in GaN and AlGaN materials and devices such as high electron mobility transistors and lightemitting diodes is presented. A comparison of theoretical and experimental threshold displacement energies is given, along with a summary of energy levels introduced by different forms of radiation, carrier removal rates and role of existing defects. Many studies have shown that GaN is several orders of magnitude more resistant to radiation damage than GaAs, i.e., it can wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 114 publications
0
6
0
Order By: Relevance
“…[1][2][3][4] When these devices are used for aerospace and military applications, such as satellites, communication equipment or detectors, they are usually suffering from the radiation damage caused by the proton, electron, neutron and γ-ray irradiation. [5][6][7][8][9][10][11][12] The irradiation of these high-energy particles usually causes the formation of point defects, defect-pairs, defect-complexes and even disorder regions in the semiconductor lattices. 5,7 Although it was shown that GaN has a relatively large displacement energy Ed (Ed (Ga) = 18 eV, Ed (N) = 22 eV) when compared to CdTe and GaAs, 6,[13][14][15] which means GaN can have a high radiation hardness, the irradiation of the high-energy particles may still cause the formation of various defects and change the concentration of equilibrium defects formed during growth 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] When these devices are used for aerospace and military applications, such as satellites, communication equipment or detectors, they are usually suffering from the radiation damage caused by the proton, electron, neutron and γ-ray irradiation. [5][6][7][8][9][10][11][12] The irradiation of these high-energy particles usually causes the formation of point defects, defect-pairs, defect-complexes and even disorder regions in the semiconductor lattices. 5,7 Although it was shown that GaN has a relatively large displacement energy Ed (Ed (Ga) = 18 eV, Ed (N) = 22 eV) when compared to CdTe and GaAs, 6,[13][14][15] which means GaN can have a high radiation hardness, the irradiation of the high-energy particles may still cause the formation of various defects and change the concentration of equilibrium defects formed during growth 12 .…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] The irradiation of these high-energy particles usually causes the formation of point defects, defect-pairs, defect-complexes and even disorder regions in the semiconductor lattices. 5,7 Although it was shown that GaN has a relatively large displacement energy Ed (Ed (Ga) = 18 eV, Ed (N) = 22 eV) when compared to CdTe and GaAs, 6,[13][14][15] which means GaN can have a high radiation hardness, the irradiation of the high-energy particles may still cause the formation of various defects and change the concentration of equilibrium defects formed during growth 12 . As a result of the high energy of the irradiation particles, some high-energy defects such as the point defects that do not form during the growth, some defect-pairs or defect-complexes may be formed during the collision cascade following the primary knock-on atom (PKA) event, e.g., it was shown in GaN that the concentration of (N-N)N split interstitial defects increases after the high dose of proton irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…[ 182 ] The strong SnO bonding might also overturn the effect of additional structural defects or create oxygen vacancies. [ 38,184 ] A‐ZTO (4:1) based electronic device with a V th shift of −6.3V exhibited a doubled mobility after a proton irradiation dose of 10 15 cm −2 , [ 13 ] revealing the stability of the metal‐oxygen bonding (Figure 10d). Furthermore, the device performance can be improved by using an organic semiconductor layer to protect the oxide semiconductor film.…”
Section: Radiation Effect On Thin Films Transistor (Tft)mentioning
confidence: 99%
“…Efforts to address these issues have been underway over the past two decades. Substantial progress has also been made in designing radiation‐hard thin films transistors (TFTs) with ZnO, Ga 2 O 3 , In 2 O 3 , SnO 2 , IGZO, SiC, GaN, and many other WBGs, [ 17–50 ] which are used in the CMOS integrated circuits (ICs) over a long period under various radiations. Emerging memory technologies were also developed to stabilize the data storage performance in high temperatures and extremely harsh environments.…”
Section: Introductionmentioning
confidence: 99%
“…A fundamental understanding of the reliability and failure mechanisms in these devices is critical to further technology development and insertion. Of particular interest is the potential to be highly resistant to radiation damage, making them ideal for use in microwave power amplifiers and DC/DC converters in space-based applications [1][2][3]. To investigate the mechanisms of radiation-induced degradation in AlGaN/GaN HEMTs, 2MeV protons were used to simulate the space radiation environment.…”
Section: Introductionmentioning
confidence: 99%